A Study of Empowerment of Employees and Organizational Effectiveness in the J&K Bank Pvt. Ltd.: A Case of Poonch District - Sharma, Dr. Alka (International Journal of Computer Sciences and Engineering, 2025)
The purpose of the study is to analyze the empowerment of the employees and the organizational effectiveness in the organization. The study was done on how they the employees get themselves empowered in the organization with different methods and how these employees get their work for the organizational effectiveness. The study is based on the survey basis. The population of the study is on the J&K Bank employees. Primary data were used for this study. Data were collected through a questionnaire that was administered to the selected respondents. The hypothesis is proved with the interpretation. The conclusion drawn from the study is that the employees get are satisfied with their working conditions and the proper decision making with which they totally committed themselves for the organizational effectiveness. Their performance will also enhance their empowerment in the organization. They are totally involved in the achievement of the goal achievement of the organization